Vitamin D Intoxication and Nephrocalcinosis in a Young Breastfed Infant - Abdullah Al-Kandari; Hussain Sadeq; Rita Alfattal; Maryam AlRashid; Mayra Alsaeid (Case Reports in Endocrinology)
Numerous studies were performed assessing the benefits and side effects of vitamin D. Vitamin D helps in regulating the calcium and phosphate metabolism leading to a healthy mineral and bone development. Vitamin D intoxication is an uncommon event that leads to hypercalcemia which can be associated with both immediate and late morbidities that can cause severe renal complications. Here, we present a case of a 4-month-old girl with a history of decreased feed and activity due hypercalcemia and high vitamin D level, which led to nephrocalcinosis. The patient received IV fluids, IV diuretics, methylprednisolone, and bisphosphonate in order to normalize the calcium level in blood. With clear verbal and written instructions for the dosage and administration of vitamin D supplements, as well as clear warnings of the potential risks of overdose, vitamin D intoxication could be an easily avoidable condition.